2021
DOI: 10.1101/2021.07.05.21259867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tocilizumab and sarilumab alone or in combination with corticosteroids for COVID-19: A systematic review and network meta-analysis

Abstract: Objective: To compare the effects of interleukin-6 (IL-6) receptor blockers, with or without corticosteroids, on mortality in patients with COVID-19. Design: Systematic review and network meta-analysis Data sources: WHO COVID-19 database, a comprehensive multilingual source of global covid-19 literature, and two prospective meta-analyses Study selection: Trials in which people with suspected, probable, or confirmed COVID-19 were randomized to IL-6 receptor blockers (with or without corticosteroids), cortic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In a linked BMJ Medicine paper (doi:10.1136/bmjmed-2022-000144), Zeraatkar and colleagues conducted a systematic review and network meta-analysis including 36 trials and 19 350 patients to help answer these questions. 4 In their network meta-analysis, Zeraatkar and colleagues combined both direct and indirect comparisons of corticosteroids, tocilizumab, and sarilumab use for severe or critical covid-19. 4 The scope of this study serves to increase the breadth of randomised trial data considered, thus generating more relevant effect estimates than conventional static, pairwise meta-analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a linked BMJ Medicine paper (doi:10.1136/bmjmed-2022-000144), Zeraatkar and colleagues conducted a systematic review and network meta-analysis including 36 trials and 19 350 patients to help answer these questions. 4 In their network meta-analysis, Zeraatkar and colleagues combined both direct and indirect comparisons of corticosteroids, tocilizumab, and sarilumab use for severe or critical covid-19. 4 The scope of this study serves to increase the breadth of randomised trial data considered, thus generating more relevant effect estimates than conventional static, pairwise meta-analysis.…”
mentioning
confidence: 99%
“…4 In their network meta-analysis, Zeraatkar and colleagues combined both direct and indirect comparisons of corticosteroids, tocilizumab, and sarilumab use for severe or critical covid-19. 4 The scope of this study serves to increase the breadth of randomised trial data considered, thus generating more relevant effect estimates than conventional static, pairwise meta-analysis. The researchers found that, in combination with corticosteroids, tocilizumab probably reduces mortality (odds ratio 0.79, 95% credible interval 0.70 to 0.88, moderate certainty of evidence) and sarilumab could reduce mortality (0.73, 0.58 to 0.92, low certainty of evidence).…”
mentioning
confidence: 99%
“…In the RECOV-ERY trial patients allocated to tocilizumab were more likely to be discharged from the hospital alive within 28 days and had a lower risk of invasive mechanical ventilation or death [21]. Overall, based on the results of REMAP-CAP and RECOVERY trials the use of tocilizumab and sarilumab in combination with dexamethasone was recommended in certain hospitalized patients who are exhibiting rapid respiratory decompensation due to COVID-19 [22].…”
Section: Discussionmentioning
confidence: 99%
“…In one systematic review, the role of sarilumab as a potential regimen has been investigated for the treatment of COVID-19 patients, and it has been concluded that sarilumab is a safe and efficient drug with good clinical outcomes ( Chamlagain et al, 2021 ). Also, a network meta-analysis demonstrated that sarilumab and tocilizumab alone or in combination with standard care such as corticosteroids might have similar effects and probably decrease the mortality rate in severe COVID-19 patients ( Zeraatkar et al, 2021 ). In one double-blind and placebo-controlled phase III clinical trial, the efficacy and safety of levilimab have been investigated in severe COVID-19 patients who do not need mechanical ventilation, and it was shown that administration of levilimab combined with standard treatment leads to an enhanced sustained clinical improvement rate ( Lomakin et al, 2021 ).…”
Section: Interventionsmentioning
confidence: 99%